Impact Assessment of Urethral Meatus Morphology and Penile Biometry in Transurethral Prostate and Bladder Surgery - Rodrigo Ribeiro Vieiralves; Paulo Henrique Pereira Conte; Eduardo Medina Felici; Nádia Cristina Pinheiro Rodrigues; Tomás Accioly de souza; Francisco J. B. Sampaio; Luciano Alves Favorito (Advances in Urology)
Objective. To analyze the penile and urethral meatus biometry and its correlation with meatoplasty during endoscopic resections. We also propose a new classification for urethral meatus morphology. Materials and Methods. We prospectively studied 105 patients who underwent prostate and bladder transurethral resections. We performed standardized measurement of penile and urethral meatus biometry followed by penile photo in the front position. The need to perform meatoplasty or dilatation during resectoscope introduction was registered. Data were analyzed comparing the correlation between two groups: without intervention (Group A) and with intervention (Group B). Results. We observed in Group A and Group B, respectively, the average length of urethral meatus of 1.07 cm versus 0.75 cm (p<0.001) and average width of urethral meatus of 0.59 cm versus 0.38 cm (p<0.001). Considering the morphology of the urethral meatus, we propose a new classification, in the following groups: (a) typical; (b) slit; (c) point-like; (d) horseshoe; and (e) megameatus. The point-like meatus was the one that most needed intervention, followed by the slit and the typical meatus (p<0.001). Conclusions. Point-like and slit-shaped urethral meatus, as well as reduced length and width of the urethral meatus, are the determining factors.